BASIC ELEMENTS IN THE SYSTEM OF GUARANTEEING THE VIGOR, SAFETY OF THE GROWER AND THE IMMEDIATE ASSESSMENT OF THE PROBLEMS OF THE VIGOR OF GRUB PRODUCTS - Прилипко, Татьяна; Букалова, Наталья (Modern engineering and innovative technologies, 2023)
It is very important to maintain the stability of the quality of food products. The buyer is interested in the methods, techniques and materials with which the manufacturer ensures the stated expiration date. Trust in the manufacturer can quickly collapse